Implementasi Web Service untuk Aplikasi Pemantau Coronavirus Disease 2019 (COVID-19) - Faisal Al Isfahani; Fuji Nugraha; Rifki Mubarok; Alam Rahmatulloh (Informatika Universitas Siliwangi, 2020)
The SARS-CoV-2 coronavirus outbreak, or commonly abbreviated as Covid-19, is currently almost paralyzing human life in various sectors. Compared to other coronaviruses such as SARS-Cov and MERS-Cov, Covid-19 spreads very quickly in multiple countries and regions. Also, the difficulty of information obtained accurately and in real-time for the community. The role of information technology is vital for the community in monitoring the coronavirus. This research utilizes web service technology to collect data and integrate services from various sources. The protocol and web service architecture used is representational state transfer (REST), with independent data exchange using the JSON format. Web service is made with node.js as well as android applications using an android studio. The results of this study have obtained a mobile-based android application that can present covid-19 data accurately and in real-time. Data recapitulation coronaviruses distribution from four service sources that have been integrated can display globally and locally in Indonesia.